The Application of Murābaha Contract in Islamic Banking from Muslim Jurists’ Perspective - Mohammad Ghazali (Universitas Darusssalam Gontor, 2018)
High needs of the society needs on Islamic banking services tends to be viewed by bankersto produce more products that can be used to answer the need of financing and easy transactionacted by people. Hence, one of the Islamic banking transaction that attracts the society enthusiastic to be used is murābaha. In theory, the murābaha is allowed in Islam, therefore thesociety want to use it, but it may be in practice of murābaha can be found the prohibitedtransaction such as riba, gharar, and gambling. By then, this paper attempts to analyse thepractice of murābaha in Islaminc banking from the thought of Muslim jurists either classicalor contemporary time. The method used for the study is comparative analysis on law producedby the Muslim jurists such as al-Mãlikiyah, al-Shafi‘iyah, al-hanafiyyah, and al-Hanãbilah.